RELATIONSHIP BETWEEN CHILDREN PARENTS AND SELF-REGULATION WITH CYBERBULLYING TRENDS IN ADOLESCENTS - Muarifah, Alif (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the relation between the attachment of child-parents and self-regulation with the tendency of cyberbullying in adolescents. This research involved 174 students in Yogyakarta City. The respondents filled out parent- child attachment scale, self-regulation scale and cyberbullying tendency scale. This study use a quantitative correlational approach with multiple linear analysis technique. The analysis of major hypothesis shows that the attachment of parent- child and self-regulation correlate very significantly with cyberbullying tendency of 0.302 (p <0.00). The analysis of minor hypothesis show that the attachment of parent-childnegatively correlated and very significant with the cyberbullying tendency of -0.230 (p <0.00). Self-regulation negatively related and highly significant with the cyberbullying tendency of -0.224 (p <0.00).